Influence of Red Mud Proportion on Circular Concrete-Filled Steel Tubular Short Columns. (24th August 2020) - Bin, Wu; Zhuoying, Tan; Fan, Li; Sun, Wang
Abstract : Tests on twelve circular concrete-filled steel tube stub columns with mixed red mud and three circular concrete-filled steel tube stub columns to investigate the influence of the mixed proportion of red mud on the mechanical behavior of axial compressive circular concrete-filled steel tube stub columns are reported. It is found that with the increase of red mud content, the ultimate load increases first and then decreases; on the contrary, the ultimate displacement decreases first and then increases; the specimen stress reaches the proportion limitation as the steel tube longitudinal strain is around 160 μ ε and reaches the yield limitation as the steel tubes' longitudinal strain is around 4400∼5000 μ ε . The axial compressive bearing capacity empirical formulation of concrete-filled steel tubes stub columns mixed with red mud is proposed. The theoretical calculation results agree well with those experimental data.